World of Words: A One Stop Web-based Application that Empowers Users to Write and Publish Their Work - Sai Krishna, Derangula; Banu Prasad, Gandla; Sreekala, K.; Sujini, G. Naga; Nagesh, A. (Journal of Knowledge in Data Science and Information Management, 2025)
World of Words is an all-encompassing website developed to allow both writers and readers to express their creativity and publish online comfortably. The platform provides users with a rich text editor with modifying tools, autosave, and font flexibility, and it allows the development and sharing of poems, blogs, stories, and novels. World of Words, which places a crucial focus on community and collaboration, offers tools like authors dashboard, user authentication, separate loggings for author and user, responding (likes and comments), enjoying, and collaboration modes that let authors get suggestions without affecting content ownership. The system consists of innovative capabilities that enhance content quality and visibility, like an offline draft mode, AI-driven plagiarism detection, and SEO optimization suggestions for improvement. Emerging content, featured blogs, and literary works are presented on a dynamic homepage via interactive animations and real-time search functionality. In addition to that, having a page where you can see the top 50 books with two options read and book now associated with search functionalities. A dynamic homepage with two sections trending and latest blogs with 50+ blogs in latest and 20+ in trending for improving user readability.